2017
DOI: 10.1093/femsyr/fox087
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of calorie restriction and calorie excess for the physiological parameters of the yeast Saccharomyces cerevisiae cells

Abstract: Glucose plays an important role in cell metabolism and has an impact on cellular physiology. Changes in glucose availability may strongly influence growth rate of the cell size, cell metabolism and the rate of generation of cellular by-products, such as reactive oxygen species. The positive effect of low glucose concentration conditions-calorie restriction is observed in a wide range of species, including the Saccharomyces cerevisiae yeast, yet little is known about the effect of high glucose concentrations-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 61 publications
7
24
0
8
Order By: Relevance
“…On the one hand, high glycolytic flux will favor fermentation and production of building blocks; on the other hand, it will reduce respiration capabilities. Hence, it is observed that ATP is produced by respiration at low glucose uptake rate [ 52 , 53 ], which is consistent with our observations (this study) and [ 12 ]. It turn, high glucose uptake rate and high glycolytic flux will correspond to higher biosynthetic rate.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…On the one hand, high glycolytic flux will favor fermentation and production of building blocks; on the other hand, it will reduce respiration capabilities. Hence, it is observed that ATP is produced by respiration at low glucose uptake rate [ 52 , 53 ], which is consistent with our observations (this study) and [ 12 ]. It turn, high glucose uptake rate and high glycolytic flux will correspond to higher biosynthetic rate.…”
Section: Discussionsupporting
confidence: 92%
“…Consistently with previous findings [ 43 , 45 ], cells lacking HXK2 display increased reproductive potential ( Figure 1 B,C) together with increased respiration (evidenced by the high level of ATP, high value of MMP and developed mitochondrial network— Figure 2 A,B and Figure 3 A–D). However, other observations in the case of Δ hxk2 strain, such as decreased rate of glucose uptake [ 12 ]; disturbing in glucose repression even in high glucose media (this study); the MMP analysis; mitochondrial morphology; and ATP level, in used conditions and rho 0 cells ( Figure 3 A–D and Figure 2 A–D) led to the assumption that increased reproductive potential ( Figure 1 A–C) is not a direct result of increased respiratory metabolism. But it may be a consequence of changes in metabolic fluxes in central carbon metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calorie restriction (CR) is a practice of limiting nutrient intake without malnutrition known to extend lifespan in a wide spectrum of organisms, ranging from yeast to primates [68][69][70]. In yeast, CR is generally imposed by reducing the glucose concentration in the growth medium from 2% to 0.5-0.2%: a growth condition that sustains growth as well as 2% glucose [71,72]. In this context, much work has been done on potential mechanisms by which glucose levels may affect Sir2 enzymatic activity.…”
Section: Nam: a Problem Or Resource For Replicative Aging?mentioning
confidence: 99%